2013
DOI: 10.3109/02770903.2012.757774
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of Wheezing and its Association with Body Mass Index and Abdominal Obesity in Children

Abstract: The results suggest that an excess of fat deposits, either in the abdominal region or elsewhere in the body, increased the risk of wheezing. Since obesity is an important public health problem worldwide, control of this problem may partially reduce the occurrence of wheezing in youth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 49 publications
1
13
0
Order By: Relevance
“…This prevalence resembles those mentioned in other studies involving adolescents, such as those conducted by Silva et al 24 . do Conde, Bahia, who detected the prevalence of 10.6% utilizing the response of the presence of chest wheezing in the 12 months and the report of asthma or wheezing at some point in life to define asthma symptoms.…”
Section: Discussionsupporting
confidence: 69%
“…This prevalence resembles those mentioned in other studies involving adolescents, such as those conducted by Silva et al 24 . do Conde, Bahia, who detected the prevalence of 10.6% utilizing the response of the presence of chest wheezing in the 12 months and the report of asthma or wheezing at some point in life to define asthma symptoms.…”
Section: Discussionsupporting
confidence: 69%
“…= 28; I 2 = 64%; 95% CI: 46–76%). When meta‐analysis was carried out on 21 studies that presented adjusted risk estimates of overweight on childhood wheezing disorders, the summary risk estimate was slightly accentuated (OR = 1.30, 95% CI: 1.19–1.42; p < 0.001) whereas the between‐study heterogeneity substantially decreased (Q = 27, d.f. = 20, p = 0.12; I 2 = 27%, 95% CI: 0.0–57%) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 29 studies presented data on the number of cases and non-cases in the overweight and normal BMI groups that included a total of 1,075,042 children (7,8,(41)(42)(43)(44)(45)(46)(50)(51)(52)(53)(54)(55)(56)(57)(58)(59)(60)(61)(62)(63)(64)(65)(66)(67)(68)(69). The summary of the ORs showed that there was a significant increased risk of wheezing disorders (OR: 1.23, 95% CI: 1.17-1.29; p < 0.001) ( Fig.…”
Section: Overweight and Childhood Wheezing Disordersmentioning
confidence: 99%
“…Later several researches published from 2011 to 2014 state that wheezing and BA correlate with a larger waist circumference and a smaller waist-to height ratio [33,43,49].…”
Section: Resultsmentioning
confidence: 99%